Pelatihan Penerapan Prinsip Koperasi dan Manfaat Koperasi dalam Rangka Meningkatkan Partisipasi Bagi Anggota Koperasi di PRIMKOP B 07 SETYA ANDIKA KODIM 0729- Bantul Daerah Istimewa Yogyakarta - Lely Savitri Dewi (E-Coops-Day, 2023)
Member participation will grow and be sustainable if members are motivated to always contributeas both owners and users of cooperative services. This motivation arises from member satisfactionwith cooperative services, in this case it is important for cooperative members to feel the benefits of cooperating both directly and indirectly. With the existence of these variables, the sustainability of the cooperative business will be guaranteed to operate according to the rules and operational basis based on cooperative principles. In order to instill awareness among members of the dual position of members in cooperatives so that they can participate actively, training is held for members of cooperatives at PRIMKOP B 07 SETYA ANDIKA Kodim 0729 - Bantul DIY in collaboration with the Indonesian Cooperative University as a series of Field Practice activities for Ikopin University Student Academic Year 2023/2024 in the context of lecturer and student service to the community in the Special Region of Yogyakarta (DIY).